2002
DOI: 10.1128/aac.46.10.3323-3326.2002
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Synergistic Interaction between Amphotericin B and Pentamidine against Scedosporium prolificans

Abstract: To develop new approaches for the treatment of invasive infections caused by Scedosporium prolificans, the in vitro interaction between amphotericin B and pentamidine against 30 clinical isolates was evaluated using a checkerboard microdilution method based on the National Committee for Clinical Laboratory Standards M38-P guidelines. The interaction between the drugs was analyzed using fractional inhibitory concentration index (FICI) analysis and response surface modeling. Amphotericin B alone was inactive aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 24 publications
1
21
0
1
Order By: Relevance
“…Some investigators have suggested using a combination of the FICI and RSM approach and have shown that results obtained from the two correlate well (2,222,223). However, the inherent complexity of the RSM method makes it less attractive as the primary method to evaluate the interactions between antifungal agents in combination, and the FICI method has remained the method of choice for most studies.…”
Section: Checkerboard Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigators have suggested using a combination of the FICI and RSM approach and have shown that results obtained from the two correlate well (2,222,223). However, the inherent complexity of the RSM method makes it less attractive as the primary method to evaluate the interactions between antifungal agents in combination, and the FICI method has remained the method of choice for most studies.…”
Section: Checkerboard Methodsmentioning
confidence: 99%
“…In a recent study, the in vitro efficacy of AmB and PN, alone or in combination, against 30 clinical isolates of S. prolificans was determined by using the FICI and RSM methods (2). These investigators showed that the combination of AmB-plus-PN exhibited synergy against 28 of 30 isolates (93.3%) and aditivity for 2 of 30 isolates (6.7%), while the RSM method predicted 100% synergy (2). Although these combinations showed promise during in vitro and in vivo studies, their clinical utility can be determined only after further studies.…”
Section: Combinations Of Antifungal Antibacterial and Anticancer Agmentioning
confidence: 99%
“…S. prolificans is resistant in vitro to virtually all antifungal agents and has responded poorly to voriconazole, with only 3 of 10 patients improving (1)(2)(3)(8)(9)(10). A recent review of scedosporiosis in solid organ transplant patients reported only four survivors among 18 patients with S. prolificans infection (5).…”
mentioning
confidence: 99%
“…Administration of PNT is a well-established approach used for prophylaxis and treatment of pneumonia caused by Pneumocystis carinii, a microorganism that was recently classified taxonomically to be a fungus (21). PNT has also been shown to have in vitro activities against a variety of fungal pathogens, such as Candida albicans, Cryptococcus neoformans, Scedosporium prolificans, and Aspergillus terreus (1,2,5,20). Therefore, in this study, we evaluated the in vitro activities of PNT against 10 clinical isolates of Fusarium spp.…”
mentioning
confidence: 99%